The Effect of Local Wisdom-Based English Learning on Elementary Students’ Vocabulary Mastery (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Vocabulary acquisition is a fundamental component of English language learning because it enables students to comprehend texts and develop broader communication skills. In elementary school contexts, however, vocabulary instruction is frequently delivered through traditional teaching practices that are not closely related to students’ real-life experiences. As a result, students often face difficulties in understanding and retaining new vocabulary. One potential approach to address this issue is the integration of local wisdom into learning activities so that the materials become more contextual and meaningful for learners. Therefore, this study aims to examine how the incorporation of local cultural elements can support vocabulary development among elementary school students. This research employed a descriptive qualitative design using a library research method. The data were gathered from various academic sources, including national and international journal articles, scholarly books, and conference proceedings that discuss English language learning, vocabulary development, and the integration of local wisdom in educational practices. The collected data were analyzed through thematic analysis by identifying, comparing, and synthesizing relevant findings from previous studies. The results indicate that the use of local cultural content, such as folklore, traditional practices, and community-based contexts, can significantly support students in understanding and remembering new vocabulary items. Learning materials that reflect students’ cultural backgrounds also contribute to higher levels of learning motivation and classroom participation. In conclusion, integrating local wisdom into English learning can create a more meaningful instructional environment and effectively support vocabulary mastery among elementary school students.